Occupational exposure to organic solvents and the risk of developing testicular germ cell tumors (TESTIS study): Effect of combined exposure assessment on risk estimation - Margot Guth; Corinne Pilorget; Marie Lefevre; Astrid Coste; Aurélie Danjou; Brigitte Dananché; Delphine Praud; Olivia Pérol; Myriam Daudin; Marie-Ange Clarotti; Stéphanie Lattes; Céline Bouillon; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: Etiological factors of testicular germ cell tumors (TGCT) remain largely unknown, but a causal role of occupational exposures to solvents has been suggested. Previous studies analyzing these exposures reported discordant results, potentially related to exposure assessment methods. The aim of this study was to investigate the role of occupational exposure to solvents on the risk of developing TGCT among young men. METHODS: This study examined occupational exposures to solvents and TGCT risk based on the lifetime work histories of 454 cases and 670 controls, aged 18-45 years, of the French national TESTIS case-control study. Solvent exposure was estimated using: (i) exposure assignment by job-exposure matrix (JEM) and (ii) JEM combined with self-reported exposure data from specific questionnaires (SQ) and expert assessment (EA). Odds ratios (OR) and 95% confidence intervals (CI) were estimated using conditional logistic regression models. RESULTS: Both approaches (JEM and JEM+SQ+EA) showed a consistent association between TGCT and trichloroethylene exposure (exposed versus not exposed; JEM=OR 1.80 [95% confidence interval (CI) 1.12-2.90] and JEM+SQ+EA= OR 2.59 (95% CI 1.42-4.72). Both approaches also observed positive associations with ketone esters and fuels & petroleum-based solvents. CONCLUSION: The results suggest that some organic solvents might be involved in the pathogenesis of TGCT among occupationally exposed men. The combined use of JEM+SQ+EA seemed to limit misclassification by considering individual exposure variability and is, therefore, an appealing approach to assess occupational exposures in epidemiological studies.